Διαχωρισμός και ανάκτηση διαφορετικών φαινολικών κλασμάτων απο΄τα απόβλητα οινοποιείου με την χρήση μεμβράνων υπερδιήθησης - Μαρκουλή, Ελευθερία (Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας και Επιστήμης Τροφίμων , Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2012)
In this thesis we studied the separation and recovery of phenolic compounds from lees (winery waste) using ultrafiltration membrane technology. To carry out the experiments three different membranes were used with different molecular weight cut off; GR40PP (100 kDa), GR70PP (20 kDa) and ETNA01PP (1 kDa). Initially there was a pre-processing of the lees, which included extraction with ethanol 96% and centrifugation. Also at pre-treatment of the membranes the water permeability and the relative flux of each membrane were calculated. Two samples were analyzed (A and B), where sample A was three-times diluted sample B. Treatment of samples with the use of membranes followed, where condensates and filtrates were recovered. All samples were analyzed for chemical identification; total phenolics, total tannins, o-biphenols, phenol fractions and anthocyanins, pectin, total and reducing sugars and pH. According to the results, the permeability was highest at GR40PP and lowest at ETNA01PP and the transmittance of the solutions A and B at ETNA01PP was three to six times lower compared to the GR70PP. The membrane that presented the greatest restraint is GR70PP for both samples. Different classes of phenolic compounds such as total phenols, o-diphenols, hydroxycinnamic acid derivatives, flavonols presented different retention. Each membrane can separate different components. ETNA01RR can be used to separate hydroxycinnamic acid derivatives from flavonols and anthocyanins, GR70PP can separate monomer and polymeric anthocyanins, and GR40PP can separate pectin (which passes into the filtrate) versus phenolic compounds and sugars that are retained in the concentrate.
Keywords: Wineries; Εffluent; Οινοποιεία; Απόβλητα